Synthesis of Biologically Active Seven-Membered-Ring Heterocycles - Reekie, Tristan A.; Kavanagh, Madeline E.; Longworth, Mitchell; Kassiou, Michael (Synthesis, 2013)
Seven-membered rings that contain one or more heteroatoms are interesting motifs for organic synthesis. In addition to their synthetic interest, they play an important role in industrial and pharmaceutical chemistry with generally increased central nervous system activity when flanked by aromatic rings. Herein we report a brief summary of some key methods of preparation for seven-membered-ring heterocycles and how they have been applied to the synthesis of commercially desirable products. We then detail new methods that we have developed for the synthesis of biologically active compounds containing this motif.
Keywords: Heterocycles; fused-ring systems; medicinal chemistry; polycycles; amines